Farming forward: soybean techniques that work | Session one - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
This video captures highlights from the recent soybean farmers outreach organized under the Radio IITA Farmers Outreach Initiative. Watch how farmers are embracing new knowledge to transform their soybean cultivation and strengthen food security in their communities.